Are Quality Improvement and Downsizing Compatible? A Human Resources Perspective - Lam, Helen; Reshef, Yonatan (Relations industrielles / Industrial Relations, 1999)
Quality improvement (QI) and downsizing have been two popular initiatives to enhance firm competitiveness. When used together, the relationship between them is neither simple norstraightforward. Although there have been many separate studies of QI and downsizing, there is a paucity of empirical work on the relationship between them, and their organizational implications. This study seeks to fill this lacuna by shedding light on: (a) how employees respond to these initiatives when combined; (b) their compatibility; and (c) ways to alleviate the negative effects of one initiative on the other.